VALUATION OF LEARNING PHYSICAL EDUCATION LEARNING IN THE PANDEMIC TIME OF COVID-19 IN SMK AL-HIDAYAH I - R. Tamtomo Putranto; Abdul Sukur; Nofi Marlina Siregar (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
ABSTRACT The purpose of this study was to find out how much the effectiveness level of physical education online learning during the COVID-19 pandemic at SMK Al-Hidayah 1 Jakarta Class X students. The research method used was a descriptive qualitative researchmethod, namely a survey using Google form media which done in their respective homes. The population in this study were students of SMK Al-Hidayah 1 Jakarta. Grade X students totaling 268 students and using a sample of 38 students in the same class. This study used an instrument inthe form of a questionnaire with variables. This research includes three aspects of affective, cognitive and psychomotor. Affective here uses aresearch instrument in the form of a questionnaire to obtain research data with a total of 18 questions with answer options Strongly Agree (SS),Agree (S), Disagree (TS) Strongly Disagree (STS) Based on the results of research analysis and discussion, it can be concluded that the level ofphysical education learning during the COVID- 19 pandemic can be broken down as follows, the affective category average is 33.56, the cognitive average is 89.59 and the psychomotor is 69.41. From the three data, it was found that the average level of learning effectiveness was 67.27 with a poor category.